MEASURABLE ONE-ANASTOMOSIS DISTAL GASTRIC BYPASS IN THE REVISIONAL SURGERY AFTER SLEEVE GASTRECTOMY: NEW PROCEDURE AND OUR RESULTS - Coşkun, Halil; COŞKUN, HALIL; Yardımcı, Erkan; YARDIMCI, ERKAN (My University, 2019)
BACKGROUNDWeight regain and inadequate co-morbidity reducti on are the most important problems inthe long-term results aft er laparoscopic sleeve gastrectomy(LSG) and in these conditi onsrevisional surgery is considered.Our aim is to show the importance of total small bowellength and appropriate small bowel loop for determine the lenght of common channel forthe revision of LSG to distal gastric bypass.METHODSData from the pati ents who underwent measurable one-anastomosis distal gastricbypass(MOADGB) in the revision of LSG from May 2017 to January 2019 was retrospecti velyanalyzed.In the surgical technique; all pati ents’ small bowel lenght is measured from theligament of treitz to ileocecal valve and gastroenterostomy anastomosis was performed1/3 distal part of the total small bowel length.RESULTSSeventeen pati ents(female n=10) with a mean age of 41±2.3 years and a mean BMI of39.1±1.7kg/m2 were included in the study.The indicati ons for revisional surgery wereinadequate weight loss (n=5), weight regain (n=11) and inadequate co-morbidity reducti on(n=1).The mean total small bowel length was 10±0.3 meter.The mean operati on ti me was126.2±5.1 minutes.There was no mortality.Only one pati ent had bleeding(5.8%).Leakage wasobserved one pati ent(5.8%). The mean excess weight loss% was 54.1±4.8% aft er the follow-up period (mean 11.2±1.4 months).The mean values of iron,ferriti n,protein,vitaminB12and vitaminD were 59.7±5.6ug/dl, 106.7±25.1ng/ml, 6.8±0.1g/dl, 592±57.2pg/ml and24.9±3.1ng/ml, respecti vely.CONCLUSIONIn the distal gastric bypass procedure which performed in the revisional surgery aft er LSG,determining the common canal length by measuring the total small bowel length mightincerease the effi cacy and decrease the rates of complicati ons such as malnutriti on andvitamin defi ciencies.
Keywords: Coşkun H., Yardımcı E., -MEASURABLE ONE-ANASTOMOSIS DISTAL GASTRIC BYPASS IN THE REVISIONAL SURGERY AFTER SLEEVE GASTRECTOMY: NEW PROCEDURE AND OUR RESULTS-, 14. Laparoskopik Endoskopik Cerrahi Kongresi, Girne, Kıbrıs (Kktc), 19 - 22 Nisan 2019, no.86, ss.93